Maxxed out : TJX companies and the largest-ever consumer data breach - Walker, Russell ([London] : SAGE, 2016)
In November 2005 Fidelity Homestead, a savings bank in Louisiana, began noticing suspicious charges from Mexico and southern California on its customers' credit cards. More than a year later, an audit revealed peculiarities in the credit card data in the computer systems of TJX Companies, the parent company of more than 2600 discount fashion and home accessories retail stores in the United States, Canada, and Europe. The U.S. Secret Service, the U.S. Justice Department, and the Royal Canadian Mounted Police found that hackers had penetrated TJX's systems in mid-2005, accessing information that dated as far back as 2003. This case study discusses this topic.
Originally Published in: Walker, R. (2013). Maxxed Out: TJX Companies and the Largest-Ever Consumer Data Breach. 5-313-507. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; TJX Companies; Risk management -- Case studies